Differential expression of checkpoint markers in the normoxic and hypoxic microenvironment of glioblastomas. (12th September 2022) - Petterson, Stine Asferg; Sørensen, Mia Dahl; Burton, Mark; Thomassen, Mads; Kruse, Torben A.; Michaelsen, Signe Regner; Kristensen, Bjarne Winther
Abstract: Glioblastoma is the most common primary malignant brain tumor in adults with an overall survival of only 14.6 months. Hypoxia is known to play a role in tumor aggressiveness but the influence of hypoxia on the immune microenvironment is not fully understood. The aim of this study was to investigate the expression of immune‐related proteins in normoxic and hypoxic tumor areas by digital spatial profiling. Tissue samples from 10 glioblastomas were stained with a panel of 40 antibodies conjugated to photo‐cleavable oligonucleotides. The free oligo‐tags from normoxic and hypoxic areas were hybridized to barcodes for digital counting. Differential expression patterns were validated by Ivy Glioblastoma Atlas Project (GAP) data and an independent patient cohort. We found that CD44, Beta‐catenin and B7‐H3 were upregulated in hypoxia, whereas VISTA, CD56, KI‐67, CD68 and CD11c were downregulated. PD‐L1 and PD‐1 were not affected by hypoxia. Focusing on the checkpoint‐related markers CD44, B7‐H3 and VISTA, our findings for CD44 and VISTA could be confirmed with Ivy GAP RNA sequencing data. Immunohistochemical staining and digital quantification of CD44, B7‐H3 and VISTA in an independent cohort confirmed our findings for all three markers. Additional stainings revealed fewer T cells and high but equal amounts of tumor‐associated microglia and macrophages in both hypoxic and normoxic regions. In conclusion, we found that CD44 and B7‐H3 were upregulated in areas with hypoxia whereas VISTA was downregulated together with the presence of fewer T cells. This heterogeneous expression should be taken into consideration when developing novel therapeutic strategies.